Patients’ preferences regarding physicians’ gender: a clinical center cross-sectional study - Dagostini, Carolina Matté; Bicca, Yan De Assunção; Ramos, Miguel Bertelli; Busnello, Sabrina; Gionedis, Murillo Cesar; Contini, Natália; Falavigna, Asdrubal (São Paulo Medical Journal, 2022)
BACKGROUND: Even with the significant growth of female representation within medicine, inequality and prejudice against this group persist. OBJECTIVE: To analyze patients’ preferences regarding the gender of physicians in general and according to different specialties, and the possible reasons behind their choice. DESIGN AND SETTING: Cross-sectional study at the Clinical Center of the University of Caxias do Sul, Brazil. METHODS: Over a three-month period in 2020, 1,016 patients were asked to complete a paper-based 11-item questionnaire. RESULTS: The majority (81.7%; n = 830) of the patients did not have a preference regarding the gender of physicians in general. The preference rate for same-gender physicians was 14.0% (n = 142/1,016), and this preference was more common among female than among male patients (17.6% versus 7.0%; odds ratio, OR = 2.85; 95% confidence interval, CI = 1.80-4.52; P < 0.001). When asked about their preference for the gender of the specialist who they were waiting to see, the overall preference rate for a same-gender professional was 17.2% (n = 175). Preference for same-gender specialists was higher for specialties essentially based on pelvic or breast examination (i.e. gynecology, urology, proctology and mastology), compared with others (33.4% versus 9.7%; OR = 4.69; 95% CI = 3.33-6.61; P < 0.001). CONCLUSIONS: The patients’ model for choice of their physician does not seem to involve physicians’ gender in general or in the majority of medical specialties. The data presented in this study may make it easier to understand patients’ preferences and concerns.